Local Cellular Responses to Metallic and Ceramic Nanoparticles from Orthopedic Joint Arthroplasty Implants - Zhang L (Dove Medical Press, 2020)
Li Zhang, El-Mustapha Haddouti, Kristian Welle, Christof Burger, Koroush Kabir,* Frank A Schildberg* Clinic for Orthopedics and Trauma Surgery, University Hospital Bonn, Venusberg-Campus 1, Bonn 53127, Germany*These authors contributed equally to this workCorrespondence: Koroush Kabir; Frank A Schildberg Email koroush.kabir@ukbonn.de; frank.schildberg@ukbonn.deAbstract: Over the last decades, joint arthroplasty has become a successful treatment for joint disease. Nowadays, with a growing demand and increasingly younger and active patients accepting these approaches, orthopedic surgeons are seeking implants with improved mechanical behavior and longer life span. However, aseptic loosening as a result of wear debris from implants is considered to be the main cause of long-term implant failure. Previous studies have neatly illustrated the role of micrometric wear particles in the pathological mechanisms underlying aseptic loosening. Recent osteoimmunologic insights into aseptic loosening highlight the important and heretofore underrepresented contribution of nanometric orthopedic wear particles. The present review updates the characteristics of metallic and ceramic nanoparticles generated after prosthesis implantation and summarizes the current understanding of their hazardous effects on peri-prosthetic cells.Keywords: nanoparticles, joint arthroplasty, osteoblasts, osteoclasts, macrophages, mesenchymal stem cells